Farmers knowledge and adoption level on goat healthcare management practices in selected areas of India - Roy, R; Tiwari, R (Bangladesh Journal of Animal Science, 2017)
The study was taken up with the objective to find out the factors effecting knowledge and adoption of goat owners in healthcare management practices. The study was purposively conducted in West Bengal and Uttar Pradesh due to its high population and two highest goat meat producing states in the country. In all, 180 respondents were randomly selected for the study. The study revealed that majority of the goat owners had knowledge on different healthcare management practices but in respect to extent of adoption of these practices, it was found low. The study shows that majority of the goat owners had medium level of knowledge about healthcare management practices. The study also shows that education, landholding, mass media exposure, formal interpersonal contact and social participation are significantly and positively correlated with knowledge level whereas education, landholding, knowledge level, mass media exposure, formal interpersonal contact and social participation are significantly and positively correlated with adoption index of the goat owners in healthcare management practices. The study further reveals that mass media exposure, education, informal interpersonal contact, landholding and flock size were the main contributing factors to farmers knowledge level in healthcare management practices whereas knowledge level in healthcare management practices, formal interpersonal contact, flock size and farming experience were the main contributing factors to farmers adoption index in healthcare management practices. Thus, a holistic extension approach for goat owners needs to be taken up considering all the factors which can enhance the knowledge level in improved healthcare management practices resulting in adoption of these improved practices so that they can prevent morbidity and mortality in their farm and thereby reduce economic losses. Bang. J. Anim. Sci. 2017. 46 (2): 95-101